2015
DOI: 10.1586/14779072.2015.1037283
|View full text |Cite
|
Sign up to set email alerts
|

Bayés’ syndrome: the association between interatrial block and supraventricular arrhythmias

Abstract: The past few years have given rise to extensive research on atrial conduction disorders and their clinical relevance. Most notably, an association between interatrial block and supraventricular arrhythmias has been discovered. This disorder, recently termed 'Bayés' syndrome', has important clinical implications. In this article, the authors review normal atrial conduction and associated disorders. A particular focus is placed on Bayés' syndrome and the relationship between interatrial block and supraventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 39 publications
1
33
0
11
Order By: Relevance
“…First, advanced IAB is likely a presentation of AP‐independent atrial electrophysiological abnormalities that remain after successful AP ablation. In support of this, advanced IAB was previously reported to reflect the underlying atrial substrate with atrial fibrosis and to be associated with the development of AF . Second, advanced IAB may play a role in initiating and maintaining reentry circuits by promoting the occurrence of unidirectional block, an important mechanism in the development of AF.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…First, advanced IAB is likely a presentation of AP‐independent atrial electrophysiological abnormalities that remain after successful AP ablation. In support of this, advanced IAB was previously reported to reflect the underlying atrial substrate with atrial fibrosis and to be associated with the development of AF . Second, advanced IAB may play a role in initiating and maintaining reentry circuits by promoting the occurrence of unidirectional block, an important mechanism in the development of AF.…”
Section: Discussionmentioning
confidence: 66%
“…A prolonged P‐wave with biphasic (±) morphology in the inferior leads represents an even higher degree of IAB and has been referred to as advanced IAB . The appearance of advanced IAB is frequently associated with atrial tachyarrhythmias, and has been found to predict AF in multiple clinical scenarios . However, the role of advanced IAB in predicting the recurrence of AF after AP ablation in patients with WPW syndrome is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative ECG and clinical data were extracted from electronic patient files. Preoperative surface ECGs were screened for the occurrence of interatrial block based on the Bayes criteria …”
Section: Methodsmentioning
confidence: 99%
“…The sample‐size estimation is based on the association between IAB and AF and the following assumptions: Incidence of AF in the nonexposed population. According to recent worldwide data, the incidence of new AF in the population age >70 years in Western Europe and North America, in a 2‐year follow‐up, is estimated to be approximately 4% (for individuals with a normal P‐wave duration and the clinical characteristics defined in the inclusion criteria) Effect size of the association between the presence of IAB and AF.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, a consensus paper defined the current ECG diagnostic criteria: partial IAB (P‐wave duration ≥120 ms) and advanced IAB (P‐wave duration ≥120 ms plus biphasic [plus/minus] morphology in inferior leads II, III, and aVF). The interest in this topic has increased in recent years, and a large number of studies recently have been published regarding the prevalence of IAB and its associations with the risk of AF, ischemic stroke, and cognitive decline . However, most studies have been performed retrospectively in the general population, where, even in the presence of IAB, the incidence of AF and stroke is low.…”
Section: Introductionmentioning
confidence: 99%